The Effect of Compensation, Performance Assessment, and Career Development on Employee's Turnover Intention - Burhanudin Burhanudin; Surya Wijanarko (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
The purpose of the study was threefold: (1) to examine the effect of compensation on employees’ turnover intention; (2) to examine the effect of performance assessment on employee’s turnover intention; and (3) to examine the effect of career development on employees’ turnover intention. This study involved a hundred employees in PT. MAKP in Sleman, Daerah Istimewa Yogyakarta, Indonesia. The data were collected using a questionnaire and analyzed using the multiple linear regression techniques. This study found that compensation negatively and insignificantly affected employees’ turnover intention, while performance assessment positively and insignificantly affected employees’ turnover intention. Lastly, this study found that career development negatively and significantly affected employees’ turnover intention. Keywords : Compensation, performance assessment, career development, turnover intention